Is a Two-Year Growth Response to Growth Hormone Treatment a Better Predictor of Poor Adult Height Outcome Than a First-Year Growth Response in Prepubertal Children With Growth Hormone Deficiency? - Straetemans, Saartje; Rooman, Raoul; De Schepper, Jean (Frontiers in Endocrinology, 2021)
Objective The first year response to growth hormone (GH) treatment is related to the total height gain in GH treated children, but an individual poor first year response is a weak predictor of a poor total GH effect in children with GH deficiency (GHD). We therefore investigated whether an underwhelming growth response after 2 years might be a better predictor of a poor adult height outcome after GH treatment in children with GHD. Design and methods Height data of GHD children treated with GH for at least 4 consecutive years of which at least 2 were prepubertal and who had attained (near) adult height (nAH) were retrieved from the Belgian Register for GH treated children (n=110, 63% boys). In ROC analyses, the change in height (∆Ht) SDS after the first and second GH treatment year were tested as predictors of a poor adult height outcome defined as : (1) nAH SDS <-2.0, or (2) nAH SDS minus mid-parental height (MPH) SDS <-1.3, or (3) total ∆Ht SDS <1.0. The cut-offs for ∆Ht SDS and its sensitivity at a 95% specificity level to detect a poor AH outcome were determined. Results Eleven percent of the studied cohort had a poor AH outcome, defined by total ∆Ht SDS <1.0. ROC curve testing of the first and second year ∆Ht SDS as a predictor for total ∆Ht SDS <1.0 had an AUC >70 %. First-year ∆Ht SDS <0.41 correctly identified 42% of the patients with a poor AH outcome at a 95% specificity level, resulting in respectively 5/12 (4.6%) correctly identified poor final responders and 5/98 (4.5%) misclassified good final responders (ratio 1.0). ∆Ht SDS after 2 prepubertal years had a cut-off level of 0.65 and a sensitivity of 50% at a 95% specificity level, resulting in respectively 6/12 (5.5%) correctly identified poor final responders and 5/98 (4.5%) misclassified good final responders (ratio 1.2). Conclusion In prepubertal GH treated children with non-acquired GHD the growth response after 2 prepubertal years of GH treatment did not meaningfully improve the prediction of poor adult height outcome after GH treatment compared to first-year growth response parameters.